Improving The Learning Outcomes of IPAS Through the Application of Powtoon Media SD 3 Wergu Wetan - Andriyani, Rissa; Ismaya, Erik Aditia; Masfuah, Siti (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: The aim of this research is to describe the improvement in science and science learning outcomes for class VI students through the application of powtoon media. Powtoon media is media in the form of animated videos containing learning material. Research Methods: This research is classroom action research (PTK) which consists of 2 cycles, each cycle divided into two meetings, consisting of planning, implementation, observation, evaluation and reflection stages. The research subjects were class VI students, with data collection techniques using interviews, observation and documentation. The data analysis technique uses qualitative descriptive statistical analysis and quantitative descriptive statistical analysis. Finding/Results: The results of the research showed an increase in science learning outcomes in the science understanding element, in cycle I classical completion reached 58%